2019
DOI: 10.1111/bpa.12778
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of host tau in tau seeding and spreading in tauopathies

Abstract: Human tau seeding and spreading occur following intracerebral inoculation of brain homogenates obtained from tauopathies in transgenic mice expressing natural or mutant tau, and in wild‐type (WT) mice. The present study was geared to learning about the patterns of tau seeding, the cells involved and the characteristics of tau following intracerebral inoculation of homogenates from primary age‐related tauopathy (PART: neuronal 4Rtau and 3Rtau), aging‐related tau astrogliopathy (ARTAG: astrocytic 4Rtau) and glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(57 citation statements)
references
References 74 publications
8
49
0
Order By: Relevance
“…However, no GAIs or GOIs, but only coiled bodies, are regularly seen in WT mice inoculated with sarkosyl-insoluble fractions of GGT linked to MAPT P301T mutation, sGGT, and GGT linked to MAPT K317M mutation in our study. The exception of a few bizarre oligodendroglial inclusions following inoculation of homogenates from MAPT K317M samples does not detract from the general concept that coiled bodies are the characteristic oligodendroglial phospho-tau inclusions in WT mice inoculated with homogenates from GGT and other tauopathies [36,37,41]. This suggests that host tau is crucial to recapitulate typical inclusions in human diseases.…”
Section: Seeding and Spreading Of Ggt Tau Following Intra-cerebral Inmentioning
confidence: 87%
See 2 more Smart Citations
“…However, no GAIs or GOIs, but only coiled bodies, are regularly seen in WT mice inoculated with sarkosyl-insoluble fractions of GGT linked to MAPT P301T mutation, sGGT, and GGT linked to MAPT K317M mutation in our study. The exception of a few bizarre oligodendroglial inclusions following inoculation of homogenates from MAPT K317M samples does not detract from the general concept that coiled bodies are the characteristic oligodendroglial phospho-tau inclusions in WT mice inoculated with homogenates from GGT and other tauopathies [36,37,41]. This suggests that host tau is crucial to recapitulate typical inclusions in human diseases.…”
Section: Seeding and Spreading Of Ggt Tau Following Intra-cerebral Inmentioning
confidence: 87%
“…Moreover, although GAIs and GOIs are typical of GGT, nothing is known about the functional alterations linked to the pathology of astrocytes and oligodendrocytes. Recent studies have shown the seeding capacity of GGT homogenates in vivo and in vitro [13,36,41]. However, little attention has been paid to the characteristics of tau deposits linked to the host tau.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, it was shown that seeding is produced in neurons of the hippocampal complex, astrocytes, oligodendroglia and along fibers of the corpus callosum, fimbria and fornix following inoculation into the hippocampus of wild type using brain homogenates of ARTAG pathology (Ferrer et al, 2018). Thus, the host tau is also relevant for the seeding and spreading of tau pathology (Ferrer et al, 2020b).…”
Section: Highlights Of Pathogenesismentioning
confidence: 99%
“…In fact, the duration of the "lag-phase" is highly dependent not only on the monomer concentration and seed formation, but also on physical parameters as well as the presence of molecular chaperones. For example, when sarkosyl-insoluble fractions from AD patients or other tauopathies are analyzed in bulk experiments, the lag-phase cannot be clearly distinguished due to the high concentration of preformed fibrils and "amyloid seeds" (i.e., Ferrer et al, 2020b) in the sample and the curve is almost logarithmic. In fact, the time evolution of the "lag-phase" is also of interest for the characterization of some amyloids (i.e., MSA-derived synuclein vs. PD-derived synuclein) with different seeding as well as propagative properties (i.e., Shahnawaz et al, 2020).…”
Section: Amyloid Aggregation Studies In Loc Devicesmentioning
confidence: 99%